Synthesis and characterization of novel (oligo)thienyl-imidazo-phenanthrolines as versatile π-conjugated systems for several optical applications - Batista, Rosa Maria Ferreira (2008)
A series of new heterocyclic chromophores 3-6 were synthesised in moderate to excellent yields by condensation of 5,6-phenantroline-dione with formyl-thiophene derivatives 1-2 in the presence of ammonium acetate in glacial acetic acid. These chromophores possess a (oligo)thienyl- π-conjugated system attached to an imidazophenanthroline moiety. These derivatives were evaluated concerning their solvatochromic properties, thermal stabilities and molecular optical nonlinearities.